The Influence of Workload and Work Motivation on Teacher Performance at Public Senior High School 2 Sendawar, West Kutai Regency - Saul Saul; Ida Bagus Made Agung Dwijatenaya; Musmuliadi Musmuliadi (International Journal of Social Service and Research, 2022)
This study aims to analyze and determine partially and simultaneously the effect of workload and work motivation on the performance of teachers in Public Senior High School 2 Sendawar, West Kutai Regency and to find out the most dominant influence on the performance of teachers at Public Senior High School 2 Sendawar. This research is a quantitative study using the SPSS instrument which discusses validity and reliability testing, multiple linear regression analysis, t test, F test to determine the effect of the independent variable on the dependent variable. The results showed that workload and work motivation had a partial and simultaneous influence on teacher performance at Public Senior High School 2 Sendawar, West Kutai Regency. Through testing the coefficient of determination (Adjusted R Square) obtained a value of 0.642 or 64.2%, meaning that teacher performance is influenced by workload and work motivation of 64.2% while the remaining 35.8% is influenced by other variables outside this study. Work motivation has the most dominant influence on teacher performance at Public Senior High School 2 Sendawar, West Kutai Regency.